Noncovalent Ubiquitin Interactions Regulate the Catalytic Activity of Ubiquitin Writers. Issue 11 (November 2016) - Wright, Joshua D.; Mace, Peter D.; Day, Catherine L.
Abstract : Covalent modification of substrate proteins with ubiquitin is the end result of an intricate network of protein–protein interactions. The inherent ability of the E1, E2, and E3 proteins of the ubiquitylation cascade (the ubiquitin writers) to interact with ubiquitin facilitates this process. Importantly, contact between ubiquitin and the E2/E3 writers is required for catalysis and the assembly of chains of a given linkage. However, ubiquitin is also an activator of ubiquitin-writing enzymes, with many recent studies highlighting the ability of ubiquitin to regulate activity and substrate modification. Here, we review the interactions between ubiquitin-writing enzymes and regulatory ubiquitin molecules that promote activity, and highlight the potential of these interactions to promote processive ubiquitin transfer. Trends: The addition of ubiquitin to proteins (ubiquitylation) regulates the logic of biological circuits and therefore many aspects of cellular function. Modification of substrate proteins with ubiquitin, and the formation of polyubiquitin chains, depends upon the interaction of ubiquitin with the catalytic machinery. Regulation of protein ubiquitylation is highly varied and it is now clear that the writers of the ubiquitin code are regulated in many ways including by phosphorylation, dimerization, and binding of small molecules. Recent advances also suggest that ubiquitin itself can bind to the ubiquitin writers at noncatalytic sites to regulate their activity. These interactions have the potential to influence the processive assembly of ubiquitin chains.